Understanding online suicidal ideation in China: nationwide distribution, social determinants, and geographic variations - Zhang, Yanji; Cai, Liang; Zhu, Chunwu (Humanities & social sciences communications, 2024)
Using novel Internet search data from Baidu Index, this study examines for the first time the nationwide distribution of city-level intensity of online suicidal ideation in China and the underlying social determinants and processes. We find that the intensity of suicidal ideation shows moderate spatial clustering, decreasing from east to west nationally and from developed to less developed areas within each province. Overall, socioeconomic inequality, social fragmentation as represented by single-generation households and religiosity, and the proportion of older adults are positively associated with suicidal ideation. Social deprivation, divorce rate, and male-to-female sex ratio have significant negative effects on suicidal ideation, while marriage rate has insignificant effects. Further analyses based on geographically weighted regression suggest that the direction, magnitude, and statistical significance of the set of risk factors relevant to suicidal ideation vary by contexts and that city-specific interventions for suicide prevention are needed.